Highly Adhesive Epidermal Sensors with Superior Water‐Interference‐Resistance for Aquatic Applications - Wang, Shuai; Li, Shuo; Wang, Haomin; Lu, Haojie; Zhu, Mengjia; Wu, Xun‐En; Liang, Huarun; Liang, Xiaoping; Zhang, Yingying (Advanced functional materials, 2023)
Grand challenges exist in the fabrication of robust skin electronics that are resistant to water interference, which can play vital roles in healthcare and lifesaving in activities such as showering, surfing, and swift water rescue. Particularly, dynamic water impingement is very destructive to skin electronics by causing device–skin delamination and sensing malfunctions. Herein, an anemone‐inspired self‐adhesive epidermal sensor with superior ability to resist water interference in various aquatic environments is developed. The epidermal sensor consists of a strain sensing layer composed of interconnected graphene flakes wrapped in ultrathin Ecoflex and a self‐adhesive layer composed of semi‐crosslinked polydimethylsiloxane, which is named as an adhesive graphene encapsulated in Ecoflex (a‐G@E) sensor. The a‐G@E sensor can conformally and stably attach on the skin under the synergy effect of the ultrathin thickness and the self‐adhesive layer. Remarkably, it can maintain a highly stable device–skin interface even under extreme aquatic conditions such as intense water impingement (up to 4 m s −1 ). As examples, this study demonstrates its applications in transmitting information, controlling robotics underwater, and tracking swimming modes of a fish. It is believed that the a‐G@E sensor can play a unique role in health‐care, sports‐monitoring, and human–machine interactions, especially for aquatic scenarios.